2011
DOI: 10.21273/hortsci.46.12.1655
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Efficient Protocol for Plant Regeneration and Genetic Transformation of Tomato cv. Micro-Tom from Leaf Explants

Abstract: A simplified protocol to obtain transgenic tomato plants was established. The effects of culture media composition and Agrobacterium concentration were evaluated. The highest shoot-forming capacity index (5.6) was observed when leaf explants were cultured for 6 weeks with 2 mg·L−1 zeatin, 0.1 mg·L−1 indoleacetic acid, and 300 mg·L−1 timentin. Shoot elongation and root formation were performed in one step on growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 20 publications
1
12
0
2
Order By: Relevance
“…Several evidence lines have shown that decreased DNA methylation might promote the microspore's embryogenesis initiation in Brassica and triticale (Solís et al ., 2012, 2015; Nowicka et al ., 2019). Tomato microspores showed similar DNA methylome with leaves, and they both can be induced for plant regeneration (Segui‐Simarro and Nuez, 2007; Cruz‐Mendívil et al ., 2011). However, to our knowledge, no evidence showed the feasibility of plant regeneration from the daughter cells of asymmetric division.…”
Section: Discussionmentioning
confidence: 99%
“…Several evidence lines have shown that decreased DNA methylation might promote the microspore's embryogenesis initiation in Brassica and triticale (Solís et al ., 2012, 2015; Nowicka et al ., 2019). Tomato microspores showed similar DNA methylome with leaves, and they both can be induced for plant regeneration (Segui‐Simarro and Nuez, 2007; Cruz‐Mendívil et al ., 2011). However, to our knowledge, no evidence showed the feasibility of plant regeneration from the daughter cells of asymmetric division.…”
Section: Discussionmentioning
confidence: 99%
“…Micro-Tom and concluded that Agrobacterium suspension (OD600 nm = 0.5) along with other optimized parameters yielded the maximum TE (5.1%) culturing cotyledonary explants. Similarly, Cruz-Mendivil et al (2011) conducted transformation study and inferred that leaf explants co-infected with bacterial density (OD600 nm = 0.5) produced the maximum TE (19.1%) in tomato cv. Micro-Tom.…”
Section: Discussionmentioning
confidence: 99%
“…One-internode stem cuttings of 3 selected transgenic (T1, T4 and T7) and WT tobacco lines were rooted in 1/2 MS medium containing 1% sucrose and 0.8% agar for two weeks. Rooted plants were acclimatized on sterile vermiculite [17], transferred to pots containing 3000 ml of sterile commercial garden soil and allowed further acclimatization in the glasshouse for 12 days. They were then individually infected with approximately 10,000 Meloidogyne incognita eggs of same batch via 3 holes made around each plant root system.…”
Section: Infection Of T0 Tobacco With M Incognitamentioning
confidence: 99%